Implications of subsoil-foundation modelling on the dynamic characteristics of a monitored bridge. Issue 2 (1st February 2019) - Faraonis, Periklis; Sextos, Anastasios; Papadimitriou, Costas; Chatzi, Eleni; Panetsos, Panagiotis
Abstract: Model updating based on system identification (SI) results is a well-established procedure to evaluate the reliability of a developed numerical model. In this inverse assessment problem, soil-foundation compliance is often not explicitly considered rigorously during design and/or purely numerical assessment. The present work aims to investigate the correlation between subsoil-foundation stiffness and modal characteristics of bridges, as a means to identify a threshold beyond which rigorous subsoil modelling is a prerequisite for reliable model updating. The second Kavala Ravine Bridge, in Greece, serves as the case study for this purpose for which a reasonably reliable finite element (FE) model is developed and updated based on ambient vibration measurements. Alternative soil profiles and subsequently redesigned foundation systems are then used to examine the effect that the correspondingly variable soil compliance would have on the natural frequencies of the bridge. It is shown that soil stiffness alone is not an adequate proxy to decide on the necessity for subsoil modelling, as the foundation stiffness (particularly in cases of softer soil profiles) tends to balance the dynamic properties of the holistic soil-foundation system. The soil-foundation stiffness is therefore the key parameter that dictates the need for refined modelling of soil–structure interaction in the framework of SI-based model updating.